2022
DOI: 10.1002/aqc.3794
|View full text |Cite
|
Sign up to set email alerts
|

Catchment‐scale distribution, abundance, habitat use, and movements of European eel (Anguilla anguilla L.) in a small UK river: Implications for conservation management

Abstract: Effective conservation management of the Critically Endangered European eel (Anguilla anguilla) is hindered by incomplete understanding of distribution, abundance, and habitat requirements at the catchment scale. All habitats available to eels within a small, highly regulated river catchment, representative of many used across the species' range, were sampled using several methods (including point abundance sample electric fishing and fyke nets) and supplemented by individual telemetry to investigate movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…However, these gradual shifts have not been sufficiently considered when evaluating their habitat use. Many previous studies have examined differences in habitat use only between two or more size classes (Itakura & Wakiya, 2020; Matsushige, Yasutake & Mochioka, 2020) or between two or more life stages (Degerman et al, 2019; Kume et al, 2020; Shuai et al, 2021b; Harwood et al, 2022). These classifications make it difficult to capture gradual changes in habitat use and may lead to inaccurate evaluation of habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these gradual shifts have not been sufficiently considered when evaluating their habitat use. Many previous studies have examined differences in habitat use only between two or more size classes (Itakura & Wakiya, 2020; Matsushige, Yasutake & Mochioka, 2020) or between two or more life stages (Degerman et al, 2019; Kume et al, 2020; Shuai et al, 2021b; Harwood et al, 2022). These classifications make it difficult to capture gradual changes in habitat use and may lead to inaccurate evaluation of habitat use.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies of anguillid eels have only evaluated the habitat use within only two or more separate size classes or life stages. For example, many studies have classified individuals into ‘small’ and ‘large’ classes according to body size (Itakura & Wakiya, 2020; Matsushige, Yasutake & Mochioka, 2020) or into elver and yellow eel stages only (Degerman et al, 2019; Kume et al, 2019; Harwood et al, 2022). These classifications could make it difficult to capture gradual changes in habitat use with growth or even lead to the misevaluation of habitat use if the classifications are not appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Although rarely used across our 36 studies, sex was found to be significant in 100% (n = 4) of cases. Its low inclusion rate is probably due to difficulties in sexing eels quickly in situ, as well as sexual dimorphism which can lead to females being preferentially selected for tagging studies (Béguer-Pon et al 2018a, b) and female biased preferences for lentic, lacustrine habitats (Oliveira et al 2001;Hagihara et al 2018;Harwood et al 2022). Where investigated, monthly and seasonal variance are seen between the timing of movement behaviours between male and female eels (Todd 1981;Stuart et al 2019;Lagarde et al 2021).…”
Section: Sexmentioning
confidence: 99%